Analisis Dana Pihak Ketiga (DPK), Risiko Dan Fee Based Income (FBI) Terhadap Pembiayaan Bagi Hasil Pada Bank Umum Syariah - Muhammad Hamdan Ainulyaqin; AS Rakhmat; Sarwo Edy; Siti Maharani (Indonesian Journal of Islamic Economics and Business, 2023)
This study aims to determine the effect of Third Party Funds (TPF), risk and Fee Based Income (FBI) on Profit Sharing Financing at Islamic Commercial Banks for the period 2013-2020. In this study using quantitative methods, the data collection technique used is Non Probity Sampling. The subjects in this study were Islamic Commercial Banks with a total sample of 96 financial statements. The data analysis technique used is the Classical Assumption Test and Multiple Regression Test using the help of the IBM SPPS Statistic 21 application. The results of this study indicate that partially the TPF variable has no effect on profit sharing financing, then for the risk variable measured using the NPF (Non Performing Financing) ratio. has a negative and significant effect on profit-sharing financing, and lastly, the Fee-based Income (FBI) variable has a negative and significant effect on profit-sharing financing.